GIS in Libraries: An Overview of Concepts and Concerns - David Deckelbaum (Issues in Science and Technology Librarianship, 1999)
This article describes what a GIS is and its implications for incorporation into a library environment. It raises a variety of questions regarding staffing needs, choice of a GIS product or array of products, and the level of service that will be provided that need to be answered before deciding to make GIS available in your library.